89.4k views
2 votes
Using the equations and enthalpy values provided, which mathematical expression can be used to determine the unknown enthalpy change represented by x?

3C + 3O2 yields 3CO2 deltaH = -1182 kJ

4H2 + 2O2 yields 4H2O deltaH =-1144 kJ

C3H8 + 5O2 yields 3CO2 + 4H2O deltaH = x

3H8 3C + 4H2 H = 104 kJ

A. 104 = (-1182) - [x + (-1144)]

B.104 = x - [(-1182) + (-1144)]

C.104 = (-1182) + (-1144) + x

D.104 = x + (-1182) - (-1144)

2 Answers

5 votes

Answer:

B. 104 = x - [(-1182) + (-1144)]

Step-by-step explanation:

The unknown entahlpy change for the given equation is determined by the Hess's Law.

3C + 3O2 → 3CO2 ΔH = -1182 kJ ....(a)

4H2 + 2O2 → 4H2O ΔH =-1144 kJ ....(b)

C3H8 → 3C + 4H2 ΔH = 104 kJ ....(c)

C3H8 + 5O2 → 3CO2 + 4H2O ΔH = x ....(d)

The unknown enthalpy change x is calculated as follows,

The equation (d) is obtained by the adding equation (a), equation (b ) and equation (c) .Therefore, the value of the unknown enthalpy change x will be equal to the sum of all enthalpy change value of the respective equation.

104 = x - [(-1182) + (-1144)]

User Thomas Krieger
by
6.6k points
6 votes
In order to solve this, we need to make use of Hess' Law.

We are already given the equations and their corresponding deltaH. Using Hess' Law, we can generate this equation:
104 kJ = x - (-1182 kJ) - (-1144 kJ)

Among the choices, the answer is
B.104 = x - [(-1182) + (-1144)]
User Krish Wadhwana
by
6.3k points